2010
DOI: 10.1111/j.1467-7652.2010.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ER stress in developing rice endosperm accumulating β‐amyloid peptide

Abstract: SummaryThe common neurodegenerative disorder known as Alzheimer's disease is characterized by cerebral neuritic plaques of amyloid b (Ab) peptide. Plaque formation is related to the highly aggregative property of this peptide, because it polymerizes to form insoluble plaques or fibrils causing neurotoxicity. Here, we expressed Ab peptide as a new causing agent to endoplasmic reticulum (ER) stress to study ER stress occurred in plant. When the dimer of Ab 1-42 peptide was expressed in maturing seed under the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 52 publications
(73 reference statements)
2
85
0
Order By: Relevance
“…However, a definite interpretation in this regard can be only drawn after larger number of genomes are sequenced and analyzed. This is the first comprehensive study of rice Hsp70 superfamily, though isolated studies on mitochondrial Hsp70 and BiPs of Hsp70 family of rice are published (Qi et al 2011;Oono et al 2010). Multiple Hsp70 members were identified in various cellular compartments in rice in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a definite interpretation in this regard can be only drawn after larger number of genomes are sequenced and analyzed. This is the first comprehensive study of rice Hsp70 superfamily, though isolated studies on mitochondrial Hsp70 and BiPs of Hsp70 family of rice are published (Qi et al 2011;Oono et al 2010). Multiple Hsp70 members were identified in various cellular compartments in rice in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Under heat stress, nuclear localized Hsp70 prevented fragmentation of DNA and provided thermotolarance (Cho and Choi 2009). Qi et al (2011) reported two mtHsp70 proteins and Oono et al (2010) reported ten BiPs proteins in rice. In this study, we found that these ten BiPs consist of six Hsp70 and four Hsp110 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…While OsbZIP60 is also affected by ER stress (Oono et al, 2010;Yu et al, 2011), the roles of OsbZIP60 in the ER stress response are not as well documented as those of OsbZIP50 and OsbZIP39. Several studies have predicted that OsbZIP60 has similar functions to that of OsbZIP50 in the response to ER stress (Oono et al, 2010;Yu et al, 2011).…”
Section: Roles In Endoplasmic Reticulum (Er) Stress Responsementioning
confidence: 99%
“…Because of this gut immunity, not only IgG but also IgA is produced. 16) We previously developed a rice vaccine, 17,18) and immunized familial AD model mice (Tg2576); as a result, the antibody titer increased and Aβ accumulation in the mouse brain was prevented compared with Tg2576-fed wild type (WT) rice. 19) In this study, we immunized senescence-accelerated mouse prone 8 (SAMP) mice, a sporadic AD model, 20) with the rice vaccine.…”
Section: )mentioning
confidence: 99%
“…Thus, we quantified the accumulation of Aβ40. A standard peptide and the samples were incubated in microplates coated with the monoclonal antibody BNT77, which recognizes human and rat Aβ (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), for 1 h at 4°C. After washing five times, the plates were incubated with an HRP-conjugated antibody raised against the C-terminus of Aβ40 for 1 h at 4°C.…”
Section: )mentioning
confidence: 99%